E-CRM In Online Gaming: Creating Value For The Player - Sheidaei, Hoda (2009)
This study reviews the literature on CRM and E-CRM discussing their opportunities, objectives and features as well as Casino CRM and keys to its success or downfall. The main goal of this study is to distinguish between "Real Values" (Company Side), "Perceived Values" and "Redundant Values" (Player Side).